Authentic Assessment in Islamic Religious Education and the Pancasila Student Profile Development - Rendi Haryadi; Muhlis Muhlis; Lubna Lubna; Nurusshobah Nurusshobah (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the implementation of authentic assessment in Islamic Religious Education (PAI) and its relevance to the development of students religious character as well as the reinforcement of values within the Pancasila Student Profile. A qualitative approach was employed through library research by reviewing various academic sources, including books, journal articles, and policy documents. The data were analyzed descriptively using content analysis to obtain a comprehensive understanding of authentic assessment concepts and practices. The findings reveal that authentic assessment provides a holistic evaluation of students attitudes, knowledge, and skills through contextual and real-life-based learning activities. In the context of PAI, this approach enables teachers to better identify the internalization of religious values reflected in students behavior, such as honesty, discipline, responsibility, and respect. Furthermore, authentic assessment contributes to strengthening key dimensions of the Pancasila Student Profile, particularly faith, piety, and noble character.